A Small Church is Not a Failed Large Church – it is a Different Sort of Animal - Bowden, Andrew M. (Rural theology, 2025)
This paper encourages rural churchgoers and rural clergy to appreciate the distinctive strengths of rural churches as they find themselves in today’s society, and to celebrate those strengths. It is rooted in the context of rural Gloucestershire.